If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 18 = 6y Reorder the terms: 18 + 2x = 6y Solving 18 + 2x = 6y Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-18' to each side of the equation. 18 + -18 + 2x = -18 + 6y Combine like terms: 18 + -18 = 0 0 + 2x = -18 + 6y 2x = -18 + 6y Divide each side by '2'. x = -9 + 3y Simplifying x = -9 + 3y
| 2(x-3)=4(x-4) | | 14x^2+45x-14=0 | | 3x+42=5x-8 | | 196-4x=41x+21 | | 64x+8y=2 | | 11-8x=35-15x | | -65-10x=7x+20 | | 3(x+6)=2x-7+x | | 2x^2+2x=3 | | m+2=6m-3 | | X^2-4x=2x+7 | | 120=16t^2 | | 7x^2+21x=0 | | x^2+4x-10=0 | | 96-2x=25x+21 | | 7x^2+21=0 | | 4x-33=x | | 4(4-w)=2(15+4y) | | 9x-7x=173-35x | | 6x+63=10x-5 | | 9(4b-1)=2-(x+4) | | 3x+11=-61-9x | | 4x+5=2x^2-8 | | 120-3x=33x+24 | | 91-3x=12x+19 | | 2x^4=50x^2 | | 7-8x=37-22x | | (X+3)(x+3)=-10 | | 10x-6=13-7x | | 4v^2-25v=21 | | (7x+11)=2(5x-2) | | 3x+14=-70-9x |